The effect of trust in a brand on brand loyalty among ultra milk consumers - Herditya Wisnu Wardana (Indonesia Auditing Research Journal, 2022)
This research is aimed to study empirically the effect of trust in a brand variable which includes brand characteristic, company characteristic and consumer – brand characteristic to brand loyalty. The mark being researched is Ultra Milk, which respondents are taking from the customer of Ultra Mining. The results of this research show that the simultaneous variable of trust in a brand has a significant effect on brand loyalty, but partially they have no significant effect on brand loyalty. The effect of trust in a brand to brand loyalty is 0.433 with a significance level of 0.000. While partially, the effect of trust in a brand variable is as follows: first, the brand characteristic has a significant effect to brand loyalty with a beta coefficient of 0.310 with a significance level of 0.008, where brand characteristic has a dominant effect to brand loyalty. Consumer – brand characteristics also have significant brand loyalty with a beta coefficient of 0.228 with a significance level of 0.024. The company characteristics have no significant effect on brand loyalty with a beta coefficient of 0.191 with a significance level of 0.073. In an effort to increase brand loyalty, the company must increase and maintain customer trust in the company. Brand characteristics are one of the most dominant variables that must remain to be controlled directly by the company the company must increase and maintain the trust of customers to the company. Brand characteristics are one of the most dominant variables that must remain to be controlled directly by the company the company must increase and maintain the trust of customers to the company. Brand characteristics are one of the most dominant variables that must remain to be controlled directly by the company.